Ansatz for the quantum phase transition in a dissipative two-qubit system - Zheng, Hang (2015)
By means of a unitary transformation, we propose an ansatz to study quantum phase transitions in the ground state of a two-qubit system interacting with a dissipative reservoir. First, the ground-state phase diagram is analyzed in the presence of the Ohmic and sub-Ohmic bath using an analytic ground-state wave function that takes into account the competition between intrasite tunneling and intersite correlation. The quantum critical point is determined as the transition point from a nondegenerate to a degenerate ground state, and our calculated critical coupling strength αc agrees with that from the numerical renormalization-group method. Moreover, by computing the entanglement entropy between the qubits and the bath as well as the qubit-qubit correlation function in the ground state, we explore the nature of the quantum phase transition between the delocalized and localized states.